Surge dynamics of Aavatsmarkbreen, Svalbard, inferred from the geomorphological record. (23rd February 2016) - Sobota, Ireneusz; Weckwerth, Piotr; Nowak, Marcin
Abstract : This study investigated the surge dynamics of Aavatsmarkbreen, a glacier in Svalbard and its geomorphological impact based on remote sensing data and field observations. The main objective was to analyse and classify subglacial and supraglacial landforms in the context of glacial deformation and basal sliding over a thin layer of thawed, water‐saturated deposits. The study also focused on the geomorphological evidence of surge‐related sub‐ and supraglacial crevassing and glacier front fracturing. From 2006 to 2013, the average recession of Aavatsmarkbreen was 363 m (52 m a −1 ). A subsequent surge during 2013–2015 resulted in a substantial advance of the glacier front of over 1 km and an increase in its surface area of more than 2 km 2 . The surface of Aavatsmarkbreen was severely fractured. Significant ice‐flow acceleration was noted whereby the highest surface velocity reached 4.9 m day − 1 . The ephemeral water‐escape structures and mini‐flutings on the fine‐grained till surface that formed during the surge are indicative of high subglacial pore‐water pressure and enhanced basal sliding. Two genetic types of clast pavements occur in the marginal zone of Aavatsmarkbreen. The results of this study will help to constrain glaciological and geomorphological processes involved in surge phenomena. Understanding the scale and effects of these processes provides insight into the behaviour of fast‐flowing glaciers and ice streams and reveals their relationships with external factors.